KinoHaptics: An Automated, Wearable, Haptic Assisted, Physio-therapeutic System for Post-surgery Rehabilitation and Self-care. - Rajanna, Vijay; Vo, Patrick; Barth, Jerry; Mjelde, Matthew; Grey, Trevor; Oduola, Cassandra; Hammond, Tracy (Journal of Medical Systems, 2016)
A carefully planned, structured, and supervised physiotherapy program, following a surgery, is crucial for the successful diagnosis of physical injuries. Nearly 50 % of the surgeries fail due to unsupervised, and erroneous physiotherapy. The demand for a physiotherapist for an extended period is expensive to afford, and sometimes inaccessible. Researchers have tried to leverage the advancements in wearable sensors and motion tracking by building affordable, automated, physio-therapeutic systems that direct a physiotherapy session by providing audio-visual feedback on patient's performance. There are many aspects of automated physiotherapy program which are yet to be addressed by the existing systems: a wide classification of patients' physiological conditions to be diagnosed, multiple demographics of the patients (blind, deaf, etc.), and the need to pursue patients to adopt the system for an extended period for self-care. In our research, we have tried to address these aspects by building a health behavior change support system called KinoHaptics, for post-surgery rehabilitation. KinoHaptics is an automated, wearable, haptic assisted, physio-therapeutic system that can be used by a wide variety of demographics and for various physiological conditions of the patients. The system provides rich and accurate vibro-haptic feedback that can be felt by the user, irrespective of the physiological limitations. KinoHaptics is built to ensure that no injuries are induced during the rehabilitation period. The persuasive nature of the system allows for personal goal-setting, progress tracking, and most importantly life-style compatibility. The system was evaluated under laboratory conditions, involving 14 users. Results show that KinoHaptics is highly convenient to use, and the vibro-haptic feedback is intuitive, accurate, and has shown to prevent accidental injuries. Also, results show that KinoHaptics is persuasive in nature as it supports behavior change and habit building. The successful acceptance of KinoHaptics, an automated, wearable, haptic assisted, physio-therapeutic system proves the need and future-scope of automated physio-therapeutic systems for self-care and behavior change. It also proves that such systems incorporated with vibro-haptic feedback encourage strong adherence to the physiotherapy program; can have profound impact on the physiotherapy experience resulting in higher acceptance rate.